2010
DOI: 10.1021/es100356f
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Formulation Facilities as Sources of Opioids and Other Pharmaceuticals to Wastewater Treatment Plant Effluents

Abstract: Facilities involved in the manufacture of pharmaceutical products are an under-investigated source of pharmaceuticals to the environment. Between 2004 and 2009, 35 to 38 effluent samples were collected from each of three wastewater treatment plants (WWTPs) in New York and analyzed for seven pharmaceuticals including opioids and muscle relaxants. Two WWTPs (NY2 and NY3) receive substantial flows (>20% of plant flow) from pharmaceutical formulation facilities (PFF) and one (NY1) receives no PFF flow. Samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(151 citation statements)
references
References 33 publications
9
139
0
3
Order By: Relevance
“…In the present study, all but two of the wasted, discarded or dispensed drugs were excreted in whole or in part as active drug [18] or drug conjugates [3]. Kummerer [76] found that nearly 70% of drugs evaluated were excreted unchanged.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…In the present study, all but two of the wasted, discarded or dispensed drugs were excreted in whole or in part as active drug [18] or drug conjugates [3]. Kummerer [76] found that nearly 70% of drugs evaluated were excreted unchanged.…”
Section: Discussionsupporting
confidence: 42%
“…Recent reviews have described the occurrence and possible effects of drug residues in tissues of aquatic organisms and wildlife [5][6][7]. Pharmaceuticals are introduced into the aquatic environment from a variety of sources, such as: hospitals [2,[8][9][10][11][12]; wastewater treatment plants [13][14][15][16]; drug manufacturers [17][18][19]; livestock farms [20][21][22]; and veterinary facilities [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…1), the proportions may have been skewed by accidental or deliberate disposal of raw cocaine into the municipal sewage system. This hypothesis requires further study, but it interesting to note that even commercial drug manufacturers release large amounts of product into municipal wastewater (Phillips et al, 2010). Higher concentrations of cocaine relative to BE were also noted in wastewater from a WWTP in Ireland (Bones et al, 2007).…”
Section: Compoundmentioning
confidence: 95%
“…In 2009, for example, researchers 1,2 reported very high levels of pharmaceutical ingredients in treated effluent coming from a plant that processes wastewater from factories near Hyderabad, India. The following year, a similar discovery was made at two wastewater-treatment plants in New York, both of which received discharges from drug-production plants 3 . Now, researchers have provided the first evidence of similar problems in Europe 4 , and have linked it to sex disruption in wild fish populations found in the Dore River in France.…”
Section: By N Ata S H a G I L B E R Tmentioning
confidence: 80%